Empowering Stakeholders in Therapeutic Communication for Children with Special Needs: A Case Study at Special Harmony Inclusive School, Jakarta - Subandi, Zera Edenzwo; Surianto, Surianto; Clara, Yesica Yuliani; Janeardie, Shannen Cleverin (Universitas Syiah Kuala, 2025)
Established in September 2023, the Lentera Cita Karya Foundation aims to address the educational and therapeutic needs in an inclusive community for children with special needs by providing holistic services through the Special Harmony School in North Jakarta. The school offers tailored education for children with Autism Spectrum Disorder (ASD) and intellectual disabilities (including Down syndrome), incorporating therapeutic support such as speech therapy, occupational therapy, sensory integration, and parent-teacher skill development programs. Despite these efforts, the implementation of therapeutic communication remains a challenge for facilitators, including teachers and therapists. Issues include limited understanding of effective verbal and non-verbal communication strategies, emotional expression, and appropriate interaction in both medical and non-medical settings. To address these challenges, a community engagement program was conducted involving 12 participants, consisting of inclusive education teachers, therapists, and parents. The program utilized a Focus Group Discussion (FGD) method, followed by expert-led sessions conducted by university lecturers. Over three separate sessions, participants engaged in thematic discussions on therapeutic communication, followed by structured presentations designed to enhance their conceptual and practical understanding. The initiative identified three major challenges: communication between therapists and children with special needs, the childrens communication with their environment, and persistent societal stigma. The program succeeded in improving participants awareness, emotional sensitivity, and basic therapeutic communication strategies applicable in inclusive educational settings.